Ancaman terhadap hak privasi sebagai bagian dari hak asasi manusia di era digital - ningsih, Sri vidiya (Maliki Interdisciplinary Journal, 2026)
Human Rights (HAM) represent fundamental rights inherent in every individual from birth, which are universal in nature, inalienable, and must be guaranteed and protected by the state. One of the essential components of human rights is the right to privacy, which encompasses the protection of personal life, personal data, and freedom from unlawful interference. In the digital era, advances in information technology have provided numerous conveniences in human life; however, they have simultaneously given rise to serious threats to the protection of individual privacy. This study aims to examine the right to privacy as an integral part of human rights, including the forms of threats it faces, the factors that influence such threats, and the impacts resulting from privacy violations in the digital era. The method employed in this study is a normative juridical approach, conducted through the analysis of legislation, international legal instruments, and relevant academic literature. The findings indicate that threats to privacy are influenced by low public awareness regarding the protection of personal data, weak regulatory frameworks, and the increasing prevalence of cybercrime such as phishing and data misuse. Furthermore, the imbalance between technological advancement and the readiness of legal systems has further amplified the risk of privacy violations. The resulting impacts include economic losses, psychological disturbances, and a decline in public trust. Therefore, concerted efforts are required to enhance digital literacy, strengthen regulatory frameworks, and enforce effective legal measures in order to provide optimal protection of the right to privacy.Top of Form